Diskursus Perkembangan Formulasi Kalender Hijriah - Syarif, Muh Rasywan (ELFALAKY: Jurnal Ilmu Falak, 2018)
AbstractThis paper addresses the development of the formulation of the Hijri calendar as the embryo of the Islamic calendar. The historical calendar approach is conceived as the history of astronomy develops in the calendar user community. The calendar is well-formed according to the evolution and progress of human civilisation itself. The calendar is a product of the living system of the calendar user community both from the ethics, nation, religion and administration of the community. The advance of a civilisation retreat will also be displayed in the progress of a calendar establishment. The higher the existence of the calendar, of course, the more advanced the civilisation will be and at the same time broaden the benefits and usefulness. By using a descriptive analytical approach, this paper aims to apprehend the development of the formulation of the Hijri calendar with its methods and applications.